(untitled) (Research, Society and Development, 2022)
Objective: To compare the effects of respiratory muscle training with the use of respiratory incentives on the maximum phonatory times (MPT) of children with cleft lip and palate (CLP). Methodology: Study characterized as a controlled and randomized clinical trial. All participants were submitted to: questionnaire with identification data, Analog Manovacuometer; maximal inspiratory and expiratory pressure with Peakflow® Digital Microlife®; and postural assessment. Inclusion criteria were: subjects aged between three and 12 years with CLP who had already undergone corrective surgeries, excluding those with other malformations or intellectual disabilities. There was random allocation into two groups: ’water seal’ and ’incentive spirometer’ (Respiron Kids®), both groups underwent weekly intervention with a six-week follow-up. Participants in the ‘water seal’ group performed three sets of ten repetitions of maximum expiration in a straw positioned at 10cmH2O inside a 500ml bottle. The ’incentive spirometer’ group performed three sets of ten repetitions of maximum expiration in the mouthpiece of the equipment with equipment at level I of resistance and positioned in an inverted way with movement of the three spheres of the equipment. Results: In the total sample, there was a predominance of unilateral incisor transforamen CLP, with a high prevalence of fistula and clinical features of mouth breathing. Five subjects were allocated to each group, with improvement of MPTs in both, descriptively, as well as s/z ratio below 1, characterizing glottic hypercontraction during phonation. Conclusion: Both modalities showed an increase in MPTs of subjects with CLP, but without normalization of glottic hypercontraction in these subjects.